Proceedings of the 11th International Congress on the Archaeology of the Ancient Near East, 03-07 April 2018, Munich (Wiesbaden)
2 cilt (1. c. xi, 539 sayfa ; 2. c. ix, 677 sayfa)
Keywords: “The two volumes include 96 selected lectures presented at the “11th International Congress on the Archaeology of the Ancient Near East” (ICAANE) at LMU München in April 2018. This congress takes place every other year and is the platform for all archaeologists worldwide to present the current results of their research in and on the Near East. The timeframe comprises the Prehistoric Period, the Bronze and Iron Ages as well as the Islamic Period; the geographical frame spans the area from Western Turkey to Afghanistan, and from Georgia to Yemen. Since researchers come from 35 countries, they summarize their latest discoveries mostly in English. The ICAANE proceedings give a state of the art-insight into current research methods and problems of Near Eastern Archaeology“ --